2017
DOI: 10.3141/2651-05
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Approach for Optimizing Road Space Allocation of Bus Lanes in Multimodal Urban Networks Through Simulation Analysis

Abstract: Although multimodality has been widely studied in the literature, planning and operating bus lanes in congested urban city centers are still challenging topics for researchers and policy makers. Most existing approaches lack quantitative methods for estimating the impact of bus lanes or for optimizing the operation of bus lanes at a system level. This paper proposes a novel optimization approach for allocating road space to bus lanes in cities. The approach determines the optimal space share between the modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Based on numerical examples, the authors revealed that road degradation level, travellers' risk-aversion level, and the uncertainty of the bus waiting time affected the user equilibrium results. Zheng et al [37] employed a simulation approach to determine the optimal space share between the modes in service. The impact of a bus lane on mode usage was taken into account to aggregated mode shift phenomena under changes in the layout of dedicated bus lanes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on numerical examples, the authors revealed that road degradation level, travellers' risk-aversion level, and the uncertainty of the bus waiting time affected the user equilibrium results. Zheng et al [37] employed a simulation approach to determine the optimal space share between the modes in service. The impact of a bus lane on mode usage was taken into account to aggregated mode shift phenomena under changes in the layout of dedicated bus lanes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The latter indicator describes a set of bi-modal traffic states in the network for which high passenger production values can be achieved. A few studies apply the concept of the pMFD in the context of multi-modal transport system optimization (Zheng and Geroliminis, 2013;Amirgholy et al, 2017;Zheng et al, 2017;Zhang et al, 2018). The main focus lies on space allocation between buses and cars based on analytical formulations for the MFD.…”
Section: Introductionmentioning
confidence: 99%
“…Still, these studies mainly apply semi-analytical models to estimate the MFD. While Zheng et al (2017) aimed to assign bus lanes, their study represents an example where an optimization based on microscopic simulation is conducted. Their objective was to minimize the occurrence of congestion in the network.…”
Section: Introductionmentioning
confidence: 99%
“…With additional information on (average) vehicle occupancy levels, the 3D-MFD can then be expressed in terms of passenger travel production (in passenger-kilometers per unit time) (Geroliminis et al, 2014;Loder et al, 2017;Chiabaut, 2015). Multi-modal MFDs are a powerful tool to investigate and understand the multimodal performance of entire urban road networks (Ampountolas et al, 2017;Zheng et al, 2017;Amirgholy et al, 2017). They can be estimated using both simulation and empirical observations (Geroliminis et al, 2014;Loder et al, 2017;Castrillon and Laval, 2018;Dakic and Menendez, 2018) or derived numerically (Boyaci and Geroliminis, 2011;Chiabaut, 2015;Dakic et al, 2019).…”
Section: Introductionmentioning
confidence: 99%